The role of organizational trust and organizational support on employees’ well-being - Di Stefano, Giovanni; Venza, Gaetano; Cascio, Gandolfa; Gaudiino, Maria (La Medicina del Lavoro, 2018)
Background: in the literature, the impact of organizational trust and perceived organizational support on employees’ well-being has been mainly recognized without a distinction focused on target they refer to. Objectives: the aim of this research is rather to test the direct role of these variables as precursors of well-being, job satisfaction and turnover intentions, distinguishing both at a theoretical and empirical level, the trust and the support that stem from the team (in which employees have direct and daily interpersonal relationships, and within which they build their work experience), and trust and support that stem from organization itself. Methods: a survey study was administered to more than 1,000 employees of a Sicilian hospital. the relations between the variables were studied through the use of hierarchical regression analysis. Results: trust and perceived support are both significant predictors of mental and physical health, job satisfaction and turnover intentions. However, the support at the team level is a more important predictor, while trust is a stronger predictor at the organizational level. Conclusions: distinguishing between team and organizational levels of trust and support allows to better understand the relationship between trust and support on the one hand, and between these variables and well-being and job satisfaction on the other. practical implications, as well as future research, should therefore also refer to the different levels of such predictors.